Review of the genus Sophonia (Hemiptera: Cicadellidae) with three new species from India - Meshram, Naresh M. (Zootaxa, 2017)
A review of the genus Sophonia Melichar from India is presented. Fifteen valid species are recognized of which three new species, Sophonia tridenta sp. nov. (Sikkim: Gangtok), Sophonia vidarvya sp. nov. (Meghalaya: Barapani) and Sophonia intricata sp. nov. (Himachal Pradesh: Katrain) from India are described and illustrated. Habitus photographic illustrations, a checklist and a modified key for all species from the Indian subcontinent are provided.